Manajemen Ekstrakurikuler dalam Upaya Pengembangan Diri Santri Pondok Pesantren Al-Luqmaniyyah Yogyakarta - ahmad hinayatulohi (Sekolah Tinggi Agama Islam An-Nawawi Purworejo, 2019)
Extracurricular is a media that can be used for the self-development process of santris in Pesantren (Islamic boarding schools). Good management of extracurricular activities will develop santri according to their natural potential. Al-Luqmaniyyah Yogyakarta is a salaf boarding school that has extracurricular management. The birth of the Santri Resource Development field is one of the answers in arranging extracurricular activities in Al-Luqmaniyyah Islamic boarding schools. This study uses descriptive-qualitative analysis with the results of the study stating that the concept of extracurricular birth in Al-Luqmaniyyah is a place for self-development of students. On the other hand the goal to be achieved is as a place for santri activities in Islamic boarding schools. So that with extracurricular activities, the santri did not look for other activities outside the pesantren environment. The birth of the Santri Resource Development field is as a manager in managing existing extracurricular activities. The application of extracurricular management through four stages, namely planning, organizing, implementing, and monitoring. Whereas the results achieved include, the interest of santri in following extracurricular activities increases every year, the reduction in the number of violations of santri, self-development whose ultimate goal is the independence of santri can be seen through emotional, intellectual, social, and economic independence.